2021
DOI: 10.3390/agriculture11050462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Smallholder Farmer’s Participation in Modern Agricultural Value Chain Tactics for Facilitating Poverty Alleviation—A Case Study of Kiwifruit Industry in Shaanxi, China

Abstract: Market-based initiatives like agriculture value chain (AVC) are becoming progressively pervasive to support smallholder rural farmers and assist them in entering larger market interventions and providing a pathway of enhancing their socioeconomic well-being. Moreover, it may also foster staggering effects towards the post-era poverty alleviation in rural areas and possessed a significant theoretical and practical influence for modern agricultural development. The prime objective of the study is to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Hence, a few scholars discussed FVCs in the context of global issues, such as business strategy, knowledge, and capacity building [51,90]. The review showed that FVCs were seen more as a strategy that can be adopted to develop region's potential rather than to develop a food network at the global level [64,75,91]. Research topics often discussed by researchers related to FVC were mostly related to the development of upstream food actors.…”
Section: Food Value Chains and Their Relationship With Sustainable Lo...mentioning
confidence: 99%
“…Hence, a few scholars discussed FVCs in the context of global issues, such as business strategy, knowledge, and capacity building [51,90]. The review showed that FVCs were seen more as a strategy that can be adopted to develop region's potential rather than to develop a food network at the global level [64,75,91]. Research topics often discussed by researchers related to FVC were mostly related to the development of upstream food actors.…”
Section: Food Value Chains and Their Relationship With Sustainable Lo...mentioning
confidence: 99%
“…The study's empirical data were obtained from a household field study conducted by the team of "Kiwifruit Industry Technology System" guided by State Key Laboratory, Northwest A&F University in September-October 2018, in Cangxi, Pujiang, and Dujiangyan counties of Sichuan Province, and Meixian, Zhouzhi, and Wugong counties of Shaanxi Province (see Figure 1). Kiwifruit is an essential target for e-commerce sales as it is a high-value and high-demand agricultural product, and Shaanxi and Sichuan are the two provinces with the largest kiwifruit cultivation areas in China [4]. According to the data of China Intelligence Research Consulting, the kiwifruit planting area in Shaanxi Province was about 1.03 million mu in 2018, and the kiwifruit planting area in Sichuan Province was about 600,000 mu.…”
Section: Data Sources and Sample Characteristicsmentioning
confidence: 99%
“…Meanwhile, household characteristics included agricultural labor force, household income level, the proportion of agricultural income, and household size. The model in the study also included provinces as dummy variables to reduce the impact of regional differences, as suggested by Wang et al [84].…”
Section: Control Variablesmentioning
confidence: 99%